The Role of Institutional Agents in Promoting Transfer Access - Alicia C. Dowd; Jenny H. Pak; Estela Mara Bensimon (Arizona State University, 2013)
A growing body of research points to the important role played by "institutional agents" in facilitating college access and success for students from non-dominant racial-ethnic and low socioeconomic status groups. Applying attachment theory, this study adds to that literature by demonstrating how institutional agents can provide a secure base, in a psychological sense, for such low-status college students in the United States to make successful postsecondary transitions and develop collegiate identities. Based on the life stories of 10 low-status students who successfully transferred from a community college to a selective college or university, our narrative analysis depicts the students' collegiate identity development and how college practitioners in positions of authority were instrumental in raising their collegiate aspirations. The results demonstrate the role of college practitioners in facilitating students' postsecondary transitions and warrant the professional development of faculty and administrators as institutional agents. We conclude by providing resources for practitioners to develop their professional knowledge and capacity to act as institutional agents.